Mastering of musical rhythm by pre-school age children with speech disorders with the help of dance-correction program trainings - N.B. Petrenko (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Introduction: It is known that regular listening to specially selected music develops children's cognitive abilities. Musical influence optimizes many important functions of brain: increases mental workability; accelerates processing of information; improves short term memory. Besides, sensitivity of visual and hearing analyzers strengthens, as well as regulation of arbitrary movements; indicators of verbal and non verbal intellect improve. Purpose: to determine peculiarities of musical rhythm's mastering by pre-school age children with speech disorders with the help of dance-correction program trainings. Material: the categories of the tested children: children of age - 4-5 and 5-6 years with speech disorders and healthy pre-school age children. Children of 4-5 years' age composed: main group (n=12), control group (n=16); group of healthy children (n=24). For assessment of verbal thinking and rhythm-motor (or dance) abilities we used complex of tests of constantly increasing difficulty. Results: we found that under influence of dance-correcting exercises activation of rhythm-motor abilities and development of cognitive functions happened in children. We also found main functional peculiarities of musical rhythm's mastering by pre-school age children. It was determined that by the end of pedagogic experiment, main groups of children approached to groups of healthy peers by all tested characteristics. Conclusions: it is recommended to include correcting components (fit ball - dance gymnastic, tales-therapy, logo-rhythm trainings, and game fitness) in trainings by choreographic program.